Generic Test Automation and Keyword Driven Approach (International Journal of Engineering and Computer Science, 2014)
In software development, testing plays an important role. Hence, it is necessary to have knowledge about testing. This paper provides an idea of testing and test automation. Simplifying testing efforts is the main objective of test automation. We have presented a process of Test Automation using keyword driven approach. The input in the form of natural language is converted to machine readable code snippet and that will be executed under framework to produce reports. The technique is based upon looking for keywords that describes actions on the target and calling functions associated with those. Using this framework, we can improve reusability of automated test. The effectiveness and efficiency of testing can be increased with the help of Automating test automation.